Tanggung Jawab Pendidikan Perspektif Pendidikan Islam - Fatkhur Rohman (Intiqad: Jurnal Agama dan Pendidikan Islam, 2020)
Responsibility is human awareness behavior or actionsof intentional or unintentional, and has the meaning of awarenessmanifesting the obligation to carry it out. Humans feel responsible because they realized of the good or bad consequences of their actions, and also realize that the other requires their dedication or sacrifice. In the Islamic educationperspective, the responsibility for Islamic education is carried out by parents, teachers, schools, the environment, government and other with an interest in education world. Some aspects of the Islamic educationresponsibility that great concern are education of tawhid (faith), morals, physicality, intellect, heart (psychic), social and sexual education. This paper is an attempt to understand the responsibility of perspective educators in Islamic education, by using a literature review approach